Effect of vitamin C and/or vitamin B complex intake on some productive, physiological and reproductive traits in the female rabbits: Tamara N. Dawood and Mudhaffar N.R. AL-Saigh - Dawood, Tamara N. (The Iraqi Journal of Veterinary Medicine, 2015)
The aim of this work was to establish the vital role of using vitamin B complex and/or vitamin C in the reproduction. Twenty female rabbits were used and they were divided randomly into four equal groups, all animals were fed 100 g of concentrate pellets diet/ head. The first group was offered drinking water free of vitamins, (control group), second group was supplied with water containing vitamin C (40 mg/ 100ml water/ head), third group was supplied with water containing vitamin B complex (0.5 ml/100ml/head), and fourth group was water supplied containing 20 mg of vitamin C and 0.25 ml of vitamin B complex/100 ml water/head. At the beginning of the experiment, male rabbits were introduced to the females for mating for one hour at morning daily for two weeks before the food and water were supplied. The results revealed that, body weight of all groups increased progressively with age. The treated groups gained insignificantly more than the control group, the second and fourth group showed higher but insignificant. In second and third group caused significant increase in PCV, Hb, WBCs, lymphocyte percentage and decrease in neutrophil, monocyte and eosinophil percentages compared with the control group. However, blood glucose and serum cholesterol levels were significantly decreased (P<0.05) in second and fourth group when compared with first group. While vitamins groups caused insignificant increase in alkaline phosphatase activity enzyme. However, the treated groups showed significantly higher fertility rate and reproductive efficiency ratio compared with the control group and numerically higher in prolificacy ratio (%). But third and fourth group showed better prolificacy and reproductive efficiency ratio than the second group